The theory and practice movement in teaching learning: Lesson Study in the graduation and professionalization of Mathematics teachers - Campos Cusati , Iracema; Elisa Portes dos Santos, Neide; Campos Cusati , Raphael; Ferreira da Silva, Jailson (Seven Editora, 2023)
This essay presents an analysis of the qualitative methodology used in research in Education, and particularly in Mathematics Education, from perspectives focused on research in Teacher Training and Teacher Professional Development. The theoretical contribution that underlies this chapter is guided by the investigations of Marli André, Bernadete Gatti, Dalila Andrade, Lee Shulman and Carlos Marcelo Garcia in order to understand the intentionality of the educational matrices that permeate the theme in the intricate subject/object interaction. In the analysis developed, based on a bibliographic review of a qualitative nature, the articulation between the highlighted lines of investigation: teacher training and teacher professional development, is configured by processes that intertwine in the trajectory of teacher professionalization, which is conceived as a means of constructing the identity of teachers and professors. Professional development considers not only the intellectual aspect, but also the different ways and languages through which subjects learn and build their identities, their ways of being in the world, in contact with other people, with the environment and with society. . In this sense, our proposal is to emphasize the relevance of the qualitative approach in research due to the frequent uses, having the knowledge that the spectrum of qualitative research techniques is wide due to its high capacity to add knowledge and meanings to the phenomena studied. The established debate encourages researchers, particularly those in the area of Mathematics Education, to face the challenges established by the new educational conditions experienced in contemporary society. DOI: 10.56238/pacfdnsv1-101